The warrior : Rafael Nadal and his kingdom of clay - Clarey, Christopher (Grand Central Publishing, Hachette Book Group, 2025)
"After his award-winning look at Roger Federer, Christopher Clarey, one of the world's preeminent tennis writers, focuses his lens on Rafael Nadal, the indomitable and inspiring force of nature from Spain who has been one of the most relentless competitors in any sport. THE WARRIOR examines Nadal's mindset and most mind-blowing achievement: 14 French Open titles. Nadal has won big and won often on tennis's other surfaces en route to becoming one of the greatest players of all time: securing two Wimbledon titles on grass and four U.S. Open titles on cushioned acrylic hardcourts. But clay, the slowest and grittiest of the game's playgrounds, is where it all comes together best for his tactical skills, whipping topspin forehand and gladiatorial mindset. Clay is to Rafael Nadal what water is to Michael Phelps, which helps explain one of the most impressive individual sports achievements of the 21st century. Clarey, who has been covering Nadal since he was 17, draws on interviews over many years with Nadal and his team and with rivals like Roger Federer. But like The Master, this is not just a book about tennis. THE WARRIOR draws much wider lessons from Nadal's approach to competition"--